2023
DOI: 10.1021/acsnano.3c01760
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome-Targeting Nanomicelles for Preventing Ischemia–Reperfusion-Induced Inflammatory Injury

Abstract: Ischemia−reperfusion (I/R) injury is a disease process that affects several vital organs. There is widespread agreement that the NLRP3 inflammasome pathway plays a crucial role in the development of I/R injury. We have developed transferrinconjugated, pH-responsive nanomicelles for the entrapment of MCC950 drug. These nanomicelles specifically bind to the transferrin receptor 1 (TFR1) expressed on the cells of the blood−brain barrier (BBB) and thus help the cargo to cross the BBB. Furthermore, the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 78 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…Similarly, for aliphatic C-H stretching, the peak was at 2878 cm −1 in chitosan, 2867 cm −1 , 2950 cm −1 in ECNP, 2826 cm −1 in insulin, and 2878 cm −1 and 2950 cm −1 in ICNP [ 61 ]. The peak indicating C=O stretch (Amide-I, O=C–NHR) was found at 1642 cm −1 in chitosan, ECNP, ICNP, and 1641.99 cm −1 in insulin [ 62 ], while for N–H bend (Amide-II) it appears at 1561 cm −1 for chitosan, 1533.65 cm −1 for insulin and at 1536 cm −1 for both ECNP and ICNP [ 63 ]. In addition to these peaks, a peak at 1431 cm −1 in insulin and 1447 cm −1 in ECNP and ICNP was observed exhibiting the S=O bond [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, for aliphatic C-H stretching, the peak was at 2878 cm −1 in chitosan, 2867 cm −1 , 2950 cm −1 in ECNP, 2826 cm −1 in insulin, and 2878 cm −1 and 2950 cm −1 in ICNP [ 61 ]. The peak indicating C=O stretch (Amide-I, O=C–NHR) was found at 1642 cm −1 in chitosan, ECNP, ICNP, and 1641.99 cm −1 in insulin [ 62 ], while for N–H bend (Amide-II) it appears at 1561 cm −1 for chitosan, 1533.65 cm −1 for insulin and at 1536 cm −1 for both ECNP and ICNP [ 63 ]. In addition to these peaks, a peak at 1431 cm −1 in insulin and 1447 cm −1 in ECNP and ICNP was observed exhibiting the S=O bond [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia and reoxidation induce NLRP3 activation in BV2 microglia through ROS; this activation is, however, inhibited by the Nrf2/ARE pathway [24]. In cerebral ischemia-reperfusion injury, the NLRP3 inflammasome causes an inflammatory response; increases the levels of C-X-C motif chemokine 1, IL-1, and IL-6; and releases cathepsin B [25]. In this study, NLRP3 correlated positively with memory B cells and activated mast cells and negatively with M2 macrophages and resting dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, extending the residence time in the body through a sustained-release effect is also an key question for calcin to enhance the antagonistic effect on heart diseases. Regarding this, OpiCa1-PEG-PLGA nanomicelles were synthesized in this study based on the most common non-toxic nanocarrier PEG-PLGA polymer [ [63] , [64] , [65] ]. We found that OpiCa1-PEG-PLGA nanomicelles keep almost the same effect as OpiCa1 in antagonizing the lethal acute heart failure induced by epinephrine and caffine, and exhibit good cardiac targeting, self-stability, as well as low toxicity.…”
Section: Discussionmentioning
confidence: 99%